Polyester degradable plastic for landscape flowerpot production and preparation method thereof
By combining modified polyhydroxy fatty acid esters and rare earth strontium aluminate-coated cerium oxide core-shell powder, the problems of low-temperature brittleness, weather resistance and degradation rate of landscape flower pot materials are solved, the low-temperature toughness, UV resistance and degradation control of flower pots are improved, and the requirements for high-end landscape flower pots are met.
Patent Information
- Application Number
- CN202510867709.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2045-06-26
AI Technical Summary
Existing biodegradable polyester plastics have problems such as low-temperature brittleness, poor weather resistance, insufficient rigidity, and uncontrollable degradation rate in landscape flower pot applications, resulting in flower pots that are easily damaged, yellowed, and have a short service life.
By using modified polyhydroxy fatty acid esters and rare earth strontium aluminate to coat cerium oxide core-shell powder, combined with PLA and PBS materials, a biodegradable polyester plastic for landscape flower pot production was prepared by improving interfacial adhesion, enhancing UV resistance, and controlling degradation rate.
It significantly improves low-temperature toughness and weather resistance, maintains rigidity, achieves a controllable degradation rate, and meets the needs of high-end landscape flower pots.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable plastic production technology, specifically relating to a biodegradable polyester plastic for the production of landscape flower pots and its preparation method. Background Technology
[0002] Biodegradable plastics are increasingly widely used in packaging, daily necessities, and agricultural mulch films. Landscape flower pots, as common tools for urban greening and home gardening, are in huge demand and are often discarded or landfilled after use. Traditional plastic flower pots (such as PP and PE) are difficult to degrade, causing serious "white pollution." Therefore, developing fully biodegradable and environmentally friendly landscape flower pot materials has significant environmental importance and market value. Polyester biodegradable plastics (such as polylactic acid PLA, polybutylene succinate PBS, and polybutylene adipate / terephthalate terephthalate PBAT) are considered ideal alternatives to traditional plastics due to their good processing properties and biodegradability.
[0003] However, existing biodegradable polyester plastics used in flowerpot production still have significant shortcomings in meeting the practical needs of landscape flowerpots. Particularly prominent issues are low-temperature brittleness and poor weather resistance. Landscape flowerpots are exposed to complex climatic environments year-round (such as sun and rain, high summer temperatures, low winter temperatures, and ultraviolet radiation). Existing PLA-based materials are extremely prone to brittleness at low temperatures (<10℃) or upon impact, resulting in a high breakage rate. Simultaneously, their insufficient UV resistance leads to yellowing and powdering after prolonged exposure, causing a sharp decline in mechanical properties and severely affecting the appearance and lifespan of the flowerpots. Furthermore, while materials with better toughness, such as PBAT / PBS, offer improved low-temperature performance, their relatively high cost, insufficient rigidity leading to deformation, and accelerated aging and degradation under strong ultraviolet radiation are also problematic. Currently, there is a lack of a biodegradable polyester plastic formulation system that simultaneously possesses good rigid support (maintaining the flowerpot's shape), excellent low-temperature toughness (impact resistance and frost crack prevention), long-term weather resistance (UV resistance and prevention of yellowing and powdering), and a controllable degradation rate (ensuring stability during the service life and degradation after disposal).
[0004] The usage scenarios of landscape flower pots dictate extremely stringent requirements for the low-temperature toughness and weather resistance of the materials. This is especially true in temperate and frigid regions with distinct seasons, where winter's low temperatures cause brittleness and year-round ultraviolet radiation leads to aging and failure, which are the main causes of customer complaints and product scrapping. The shortcomings of existing technology severely restrict the application and promotion of biodegradable plastics in high-end, durable landscape flower pots.
[0005] Therefore, developing a polyester biodegradable plastic formulation and preparation method that can effectively overcome the defects of low-temperature brittleness and weather resistance while maintaining good processability, mechanical strength and controllable degradation is of great practical necessity and market urgency for promoting the large-scale application of biodegradable materials in the landscape field and reducing environmental pollution. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a biodegradable polyester plastic for the production of landscape flower pots and its preparation method. This material needs to significantly improve low-temperature toughness, effectively enhance weather resistance (especially UV resistance), maintain sufficient rigidity and strength, have a controllable biodegradation rate, and be easy to process and mold. The specific technical solution is as follows:
[0007] A biodegradable polyester plastic for the production of landscape flower pots comprises the following raw materials in parts by weight:
[0008] 50-70 parts of polylactic acid;
[0009] 20-35 parts of polybutylene succinate;
[0010] 10-15 parts of modified polyhydroxy fatty acid ester;
[0011] 0.8–1.2 parts of rare earth strontium aluminate-coated cerium oxide core-shell powder;
[0012] Antioxidant 0.3–0.8 parts;
[0013] Lubricant 0.5-1.0 parts;
[0014] The modified polyhydroxy fatty acid ester is prepared by the following steps:
[0015] Polyhydroxyalkanoate was pulverized to a particle size ≤1mm and vacuum dried at 50-80℃ for 5-6h to obtain dried polyhydroxyalkanoate. Then, maleic anhydride and dicumyl peroxide were mixed and dissolved in acetone to prepare a 10wt% modification solution. The dried polyhydroxyalkanoate was added to a co-rotating twin-screw extruder, and the modification solution was injected into it for extrusion. The resulting extruded strips were then water-cooled, pelletized, extracted with acetone, and vacuum dried to obtain modified polyhydroxyalkanoate.
[0016] Furthermore, the maleic anhydride and dicumyl peroxide are mixed at a mass ratio of 6 to 12:1.
[0017] Furthermore, the temperature gradient of the co-rotating twin-screw extruder is as follows: feeding zone 125-130℃, melting zone 140-145℃, reaction zone 150-155℃, and homogenization zone 140-150℃.
[0018] Furthermore, the rare earth strontium aluminate-coated cerium oxide core-shell powder is prepared by the following steps:
[0019] B1. Dissolve strontium nitrate and aluminum nitrate in deionized water, then add citric acid and sonicate for 20-30 minutes to obtain a strontium aluminum solution; in another container, disperse nano-cerium oxide in deionized water and sonicate for 20-30 minutes to obtain a cerium oxide suspension.
[0020] B2. Slowly add the strontium aluminum solution dropwise into the cerium oxide suspension. After the addition is complete, stir at a constant temperature of 55-60℃ for 20-30 minutes. After that, add ammonia water to adjust the pH to 9.0 and let it stand to form a gel.
[0021] B3. The gel was aged at room temperature for 24 hours, then dried at 100°C for 12 hours. After drying, it was ground through a 100-mesh sieve and then calcined in a muffle furnace at 580-600°C for 2 hours. It was then naturally cooled to room temperature to obtain rare earth strontium aluminate-coated cerium oxide core-shell powder.
[0022] Furthermore, the ratio of strontium nitrate, aluminum nitrate, deionized water, and citric acid in B1 is 0.2 mol: 0.8 mol: 500 mL: 1.0–1.2 mol; the ratio of nano-cerium oxide and deionized water in B1 is 100 g: 500 mL.
[0023] Furthermore, the antioxidant is a compound of primary antioxidant 1010 and secondary antioxidant 168 in a mass ratio of 1:1 to 2.
[0024] Furthermore, the lubricant is calcium stearate or pentaerythritol tetrastearate.
[0025] Furthermore, the preparation method of the biodegradable polyester plastic for landscape flower pot production includes the following steps: weighing each raw material according to the mass fraction, mixing polylactic acid, polybutylene succinate and modified polyhydroxy fatty acid ester for 3-5 minutes, then adding antioxidants and lubricants, and continuing to mix for 5-8 minutes to obtain a premix, then feeding the premix into a twin-screw extruder for melt extrusion, and simultaneously adding rare earth strontium aluminate-coated cerium oxide core-shell powder, and after extrusion, cooling and pelletizing the resulting melt, obtaining the biodegradable polyester plastic for landscape flower pot production.
[0026] Furthermore, the process parameters of the twin-screw extruder are as follows:
[0027] The twin-screw extruder has a screw diameter of 40 mm; a length-to-diameter ratio of 40:1; a screw speed of 200–350 rpm; and zone temperatures of the twin-screw extruder as follows: Zone 1 150–160℃, Zone 2 165–175℃, Zone 3 170–180℃, Zone 4 175–185℃, Zone 5 175–185℃, Zone 6 170–180℃, and Zone 7 165–175℃.
[0028] The beneficial effects of this invention are:
[0029] (1) Significantly improves low-temperature toughness and solves the problem of low-temperature brittleness:
[0030] Technical Background: The background technology emphasizes that existing PLA-based materials have poor impact toughness at low temperatures (<10°C), easily leading to flowerpot breakage. The test results of Comparative Example 1 and Comparative Example 2 (representing the unoptimized solution) verify this problem: the low-temperature notched impact strength of Comparative Example 1 (using unmodified PHA) is only 5.1 kJ / m. 2 Comparative Example 2 (without PHA) showed an even lower level of 4.3 kJ / m³. 2 This is far below the impact resistance requirements of flowerpots (which typically require ≥8 kJ / m³). 2 ).
[0031] The solution of this invention: Examples 7-9 significantly improved low-temperature toughness by adding 10-15 parts of modified polyhydroxyalkanoate (MAH-modified PHA). As shown in Table 1, the impact strength of Examples 7-9 was 9.8 kJ / m. 2 11.2 kJ / m 2 and 8.5 kJ / m 2 All meet the requirements (≥8.5 kJ / m³). 2 ).
[0032] Effect Analysis: Comparative Example 8 (Impact Strength 11.2 kJ / m) 2 ) and Comparative Example 1 (5.1 kJ / m 2 The impact strength was increased by 53%. This is attributed to the interfacial compatibilizing effect of MAH-modified PHA: MAH reacts with PHA during extrusion, improving the interfacial adhesion of the PLA / PBS / PHA phases and reducing stress concentration points, thereby effectively absorbing impact energy at -20°C. Comparative Example 2 (without PHA) had the lowest impact strength (4.3 kJ / m²), further demonstrating that the toughening effect of PHA is irreplaceable. Therefore, this invention effectively overcomes the low-temperature brittleness defects of existing materials, ensuring the durability of flowerpots in cold winters.
[0033] (2) Effectively enhances weather resistance and inhibits yellowing and photo-oxidative degradation:
[0034] Technical Background: Background technology indicates that existing materials are prone to yellowing and pulverization under ultraviolet radiation, resulting in a sharp decline in mechanical properties. The results of Comparative Examples 3 and 4 highlight this defect: Comparative Example 3 (using bare nano-cerium oxide) has a color difference ∆E = 6.2 (severe yellowing), while Comparative Example 4 (core-shell-less powder) has a ∆E = 7.5 (worst).
[0035] Solution of the present invention: Examples 7-9 introduce 0.8-1.2 parts of rare earth strontium aluminate-coated cerium oxide core-shell powder (SrAl2O4@CeO2) to form a core-shell structure. Table 1 shows that the color difference ∆E of Examples 7-9 is only 1.5-1.7 (almost no yellowing).
[0036] Effect Analysis: In the core-shell powder, the SrAl2O4 coating layer isolates the CeO2 core from the resin matrix, preventing CeO2 from directly catalyzing the photo-oxidation reaction (∆E=6.2 in Comparative Example 3, indicating catalysis by bare CeO2). Simultaneously, CeO2, acting as a UV absorber and free radical quencher, synergistically enhances UV resistance efficiency with SrAl2O4. Example 8 (∆E=1.6) showed a 78% reduction in color difference compared to Comparative Example 4 (∆E=7.5), demonstrating that the core-shell structure is the decisive factor in improving weather resistance. This solves the yellowing problem caused by long-term outdoor exposure of landscape flowerpots, extending their service life.
[0037] (3) Maintain high rigidity while optimizing material balance:
[0038] Technical Background: The background technology mentions that tough materials such as PBAT / PBS lack rigidity and are prone to deformation. All test groups (including comparative examples) had a flexural modulus >2000MPa, meeting the rigidity requirements of flowerpots, but Comparative Example 1 (2100MPa) and Comparative Example 2 (2050MPa) were slightly lower than the examples.
[0039] The solution of this invention: Examples 7-9 use PLA (50-70 parts) as a rigid framework, PBS (20-35 parts) as a toughening supplement, and modified PHA and core-shell powder as functional additives. Table 1 shows that the flexural moduli of Examples 7-9 are 2350 MPa, 2200 MPa and 2450 MPa, respectively.
[0040] Effect Analysis: Compared with Comparative Example 1 (2100 MPa), Example 8 (modulus 2200 MPa) showed only a slight decrease in modulus (4.5%), proving that the addition of modified PHA and core-shell powder did not sacrifice rigidity. This is due to the high modulus characteristics of PLA and the flexibility balance of PBS, ensuring the stability of the flowerpot shape. The modulus of all examples was >2200 MPa, higher than that of the comparative examples (2050-2180 MPa), indicating that the formulation of this invention optimizes the rigidity-toughness balance.
[0041] (4) Achieve a controllable degradation rate and ensure stability during the service life:
[0042] Technical Background: The background technology emphasizes that the degradation rate of existing materials is uncontrollable (too early or too slow). The high weight loss rates (25.3% and 28.5%) in Comparative Examples 3 and 4 indicate premature degradation.
[0043] Solution of the present invention: Examples 7-9 use core-shell powder to protect the matrix, and the degradation weight loss rate is controlled at 14.5%-16.8% (Table 1).
[0044] Effect Analysis: The coating layer in the core-shell structure (SrAl2O4@CeO2) blocks moisture and microorganisms, slowing down hydrolysis (comparative Example 8: weight loss 16.8% vs. Comparative Example 4: 28.5%). Simultaneously, CeO2 within the core-shell does not directly contact the resin, avoiding catalytic degradation (Comparative Example 3: weight loss 25.3% due to bare CeO2 catalysis). The weight loss rates of Examples 7-9 are all ≤16.8%, indicating that the material degrades slowly within 90 days, ensuring the stability of the flowerpot's service life (typically 1-2 years), while degradation accelerates after disposal.
[0045] Therefore, this invention achieves for the first time a synergistic improvement in low-temperature toughness, weather resistance, rigidity and controllable degradation, meeting the requirements of the background technology for "high-end, durable landscape flower pots".
[0046] In summary, this invention comprehensively addresses the core defects of landscape flowerpot materials by modifying PHA (to enhance interfacial compatibilization and low-temperature toughness) and using core-shell powder (to enhance UV resistance and degradation control), combined with a PLA / PBS base system. Example data confirms that its low-temperature impact strength is increased by more than 50%, yellowing rate is reduced by more than 80%, rigidity remains stable, and degradation rate is controllable, demonstrating outstanding environmental and market value. Detailed Implementation
[0047] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Furthermore, unless otherwise specified, the raw materials, reagents, or devices used in the following embodiments can be obtained from conventional commercial channels or by existing known methods.
[0048] Example 1
[0049] Preparation of modified polyhydroxy fatty acid esters:
[0050] A1. Preprocessing:
[0051] Polyhydroxy fatty acid ester (PHA, Ningbo Tianan Biotechnology ENMAT Y1000P, melt index 3g / 10min (160℃)) was pulverized to a particle size ≤1mm and dried under vacuum at 50℃ for 5h to obtain dried polyhydroxy fatty acid ester. Then, maleic anhydride (MAH, Sinopharm Reagent, purity 98%) and dicumyl peroxide (DCP, purity 98%) were mixed at a mass ratio of 6:1 and dissolved in acetone (industrial grade) to prepare a 10wt% modified solution.
[0052] A2. Reactive extrusion:
[0053] Using a co-rotating twin-screw extruder (L / D=40:1), set the temperature gradient:
[0054] Feeding zone: 125℃; Melting zone: 140℃; Reaction zone: 150℃ (reaction temperature ≤ 160℃ to prevent PHA degradation); Homogenization zone: 140℃; After setting, add dried polyhydroxy fatty acid ester from the main feed port, and inject the modified solution into the reaction zone through the side feed pump. The ratio of dried polyhydroxy fatty acid ester to modified solution is 1kg:100mL. Then set the screw speed to 200rpm and the residence time to 2min. Extrude the strips, cool them with water, and granulate them. Extract the resulting granules with boiling acetone for 4h (to remove unreacted MAH), and then vacuum dry them at 80℃ for 12h to obtain modified polyhydroxy fatty acid ester.
[0055] Example 2
[0056] Preparation of modified polyhydroxy fatty acid esters:
[0057] A1. Preprocessing:
[0058] Polyhydroxy fatty acid ester (PHA, Ningbo Tianan Biotechnology ENMAT Y1000P, melt index 3g / 10min (160℃)) was pulverized to a particle size ≤1mm and dried under vacuum at 60℃ for 6h to obtain dried polyhydroxy fatty acid ester. Then, maleic anhydride (MAH, Sinopharm Reagent, purity 98%) and dicumyl peroxide (DCP, purity 98%) were mixed at a mass ratio of 9:1 and dissolved in acetone (industrial grade) to prepare a 10wt% modified solution.
[0059] A2. Reactive extrusion:
[0060] Using a co-rotating twin-screw extruder (L / D=40:1), set the temperature gradient:
[0061] Feeding zone: 130℃; Melting zone: 145℃; Reaction zone: 150℃ (reaction temperature ≤ 160℃ to prevent PHA degradation); Homogenization zone: 140℃; After setting, add dried polyhydroxy fatty acid ester from the main feed port, and inject the modified solution into the reaction zone through the side feed pump. The ratio of dried polyhydroxy fatty acid ester to modified solution is 1kg:100mL. Set the screw speed to 200rpm and the residence time to 3min. Extrude strips and cut them into pellets by water cooling. Extract the resulting pellets with boiling acetone for 4h (to remove unreacted MAH), and then vacuum dry at 80℃ for 12h to obtain modified polyhydroxy fatty acid ester.
[0062] Example 3
[0063] Preparation of modified polyhydroxy fatty acid esters:
[0064] A1. Preprocessing:
[0065] Polyhydroxy fatty acid ester (PHA, Ningbo Tianan Bio ENMAT Y1000P, melt index 3g / 10min (160℃)) was pulverized to a particle size ≤1mm and dried under vacuum at 80℃ for 6h to obtain dried polyhydroxy fatty acid ester. Then, maleic anhydride (MAH, Sinopharm Reagent, purity 98%) and dicumyl peroxide (DCP, purity 98%) were mixed at a mass ratio of 12:1 and dissolved in acetone (industrial grade) to prepare a 10wt% modified solution.
[0066] A2. Reactive extrusion:
[0067] Using a co-rotating twin-screw extruder (L / D=40:1), set the temperature gradient:
[0068] Feeding zone: 130℃; Melting zone: 145℃; Reaction zone: 155℃ (reaction temperature ≤ 160℃ to prevent PHA degradation); Homogenization zone: 150℃; After setting, add dried polyhydroxy fatty acid ester from the main feed port, and inject the modified solution into the reaction zone through the side feed pump. The ratio of dried polyhydroxy fatty acid ester to modified solution is 1kg:100mL. Set the screw speed to 200rpm and the residence time to 3min. Extrude strips and cut them into pellets by water cooling. Extract the resulting pellets with boiling acetone for 4h (to remove unreacted MAH), and then vacuum dry at 80℃ for 12h to obtain modified polyhydroxy fatty acid ester.
[0069] Example 4
[0070] Preparation of rare earth strontium aluminate-coated cerium oxide core-shell powder:
[0071] B1. Preparation of solutions / suspensions:
[0072] 0.2 mol of strontium nitrate (Sr(NO3)2, Sinopharm reagent, purity 99%) and 0.8 mol of aluminum nitrate (Al(NO3)3·9H2O) were dissolved in 500 mL of deionized water. Then, 1.0 mol of citric acid was added, and the solution was sonicated for 20 min (300 W) to obtain a strontium-aluminum solution. In a separate container, 100 g of nano-cerium oxide (CeO2, particle size 50 nm, purity 99.5%) was dispersed in 500 mL of deionized water and sonicated for 20 min (300 W) to obtain a cerium oxide suspension. The nano-cerium oxide... The core functions include: (1) as a highly efficient UV absorber and free radical quencher, significantly improving the weather resistance of the material and inhibiting photo-oxidative degradation and yellowing; (2) cerium oxide particles can promote the interaction between the PLA / PBS / PHA phase interface during the melt processing, playing a certain "in-situ compatibilization" effect, improving the interfacial adhesion and reducing stress concentration points; (3) studies have found that an appropriate amount of CeO2 can induce subtle changes in the crystal morphology of PLA (microcrystal size regulation), which, together with the toughening effect of PBS / PHA, unexpectedly synergistically improves the toughness of the material at low temperatures and significantly reduces the brittle transition temperature.
[0073] B2. Coating reaction:
[0074] The strontium aluminum solution prepared above was slowly added dropwise to the cerium oxide suspension. After the addition was complete, the mixture was stirred at a constant temperature of 55°C for 20 minutes. After that, ammonia water was added dropwise to adjust the pH to 9.0, and the mixture was allowed to stand to form a gel.
[0075] B3. Aging and Calcination:
[0076] The gel was aged at room temperature for 24 hours, then dried at 100℃ for 12 hours. After drying, it was ground through a 100-mesh sieve and then calcined in a muffle furnace at 580℃ for 2 hours (heating rate 5℃ / min). It was then naturally cooled to room temperature to obtain rare earth strontium aluminate-coated cerium oxide core-shell powder.
[0077] Example 5
[0078] Preparation of rare earth strontium aluminate-coated cerium oxide core-shell powder:
[0079] B1. Preparation of solutions / suspensions:
[0080] 0.2 mol of strontium nitrate (Sr(NO3)2, Sinopharm reagent, purity 99%) and 0.8 mol of aluminum nitrate (Al(NO3)3·9H2O) were dissolved in 500 mL of deionized water. Then, 1.1 mol of citric acid was added, and the solution was sonicated for 30 min (300 W) to obtain a strontium-aluminum solution. In a separate container, 100 g of nano-cerium oxide (CeO2, particle size 50 nm, purity 99.5%) was dispersed in 500 mL of deionized water and sonicated for 30 min (300 W) to obtain a cerium oxide suspension. The nano-cerium oxide... The core functions include: (1) as a highly efficient UV absorber and free radical quencher, significantly improving the weather resistance of the material and inhibiting photo-oxidative degradation and yellowing; (2) cerium oxide particles can promote the interaction between the PLA / PBS / PHA phase interface during the melt processing, playing a certain "in-situ compatibilization" effect, improving the interfacial adhesion and reducing stress concentration points; (3) studies have found that an appropriate amount of CeO2 can induce subtle changes in the crystal morphology of PLA (microcrystal size regulation), which, together with the toughening effect of PBS / PHA, unexpectedly synergistically improves the toughness of the material at low temperatures and significantly reduces the brittle transition temperature.
[0081] B2. Coating reaction:
[0082] The strontium aluminum solution prepared above was slowly added dropwise to the cerium oxide suspension. After the addition was complete, the mixture was stirred at a constant temperature of 55°C for 30 minutes. After that, ammonia water was added dropwise to adjust the pH to 9.0, and the mixture was allowed to stand to form a gel.
[0083] B3. Aging and Calcination:
[0084] The gel was aged at room temperature for 24 hours, then dried at 100℃ for 12 hours. After drying, it was ground through a 100-mesh sieve and then calcined in a muffle furnace at 600℃ for 2 hours (heating rate 5℃ / min). It was then naturally cooled to room temperature to obtain rare earth strontium aluminate-coated cerium oxide core-shell powder.
[0085] Example 6
[0086] Preparation of rare earth strontium aluminate-coated cerium oxide core-shell powder:
[0087] B1. Preparation of solutions / suspensions:
[0088] 0.2 mol of strontium nitrate (Sr(NO3)2, Sinopharm reagent, purity 99%) and 0.8 mol of aluminum nitrate (Al(NO3)3·9H2O) were dissolved in 500 mL of deionized water. Then, 1.2 mol of citric acid was added, and the solution was sonicated for 30 min (300 W) to obtain a strontium-aluminum solution. In a separate container, 100 g of nano-cerium oxide (CeO2, particle size 50 nm, purity 99.5%) was dispersed in 500 mL of deionized water and sonicated for 30 min (300 W) to obtain a cerium oxide suspension. The nano-cerium oxide... The core functions include: (1) as a highly efficient UV absorber and free radical quencher, significantly improving the weather resistance of the material and inhibiting photo-oxidative degradation and yellowing; (2) cerium oxide particles can promote the interaction between the PLA / PBS / PHA phase interface during the melt processing, playing a certain "in-situ compatibilization" effect, improving the interfacial adhesion and reducing stress concentration points; (3) studies have found that an appropriate amount of CeO2 can induce subtle changes in the crystal morphology of PLA (microcrystal size regulation), which, together with the toughening effect of PBS / PHA, unexpectedly synergistically improves the toughness of the material at low temperatures and significantly reduces the brittle transition temperature.
[0089] B2. Coating reaction:
[0090] The strontium aluminum solution prepared above was slowly added dropwise to the cerium oxide suspension. After the addition was complete, the mixture was stirred at a constant temperature of 60°C for 30 minutes. After that, ammonia water was added dropwise to adjust the pH to 9.0, and the mixture was allowed to stand to form a gel.
[0091] B3. Aging and Calcination:
[0092] The gel was aged at room temperature for 24 hours, then dried at 100℃ for 12 hours. After drying, it was ground through a 100-mesh sieve and then calcined in a muffle furnace at 600℃ for 2 hours (heating rate 5℃ / min). It was then naturally cooled to room temperature to obtain rare earth strontium aluminate-coated cerium oxide core-shell powder.
[0093] Example 7
[0094] A method for preparing biodegradable polyester plastic for landscape flowerpot production includes the following steps:
[0095] S1. Raw material preparation (by weight):
[0096] Polylactic acid (PLA): 50 parts. Injection molding grade PLA resin with a melt index (MFI, 190℃ / 2.16kg) of 5–15 g / 10 min was selected; in this example, NatureWorksInge™ 4032D was used. PLA resin provides basic rigidity and biodegradability.
[0097] Polybutylene succinate (PBS): 20 parts. A PBS resin with an intrinsic viscosity [η] of 1.2–1.8 dL / g was selected; in this example, Showa Denko Bionolle™ 1001MD was used. PBS resin primarily provides flexibility, impact toughness, and low-temperature performance.
[0098] Modified polyhydroxy fatty acid ester: 10 parts. In this example, the modified polyhydroxy fatty acid ester prepared in Example 1 was used.
[0099] Strontium aluminate-coated cerium oxide core-shell powder (SrAl2O4@CeO2): 0.8 parts. In this example, the strontium aluminate-coated cerium oxide core-shell powder prepared in Example 4 was used.
[0100] Antioxidant: 0.3 parts. It is a compound of primary antioxidant 1010 (BASF) and secondary antioxidant 168 (BASF) in a 1:1 mass ratio. Antioxidants are used to delay the thermo-oxidative aging of materials during processing and use.
[0101] Lubricant: 0.5 parts. Calcium stearate is selected; in this example, Sinopharm Group's calcium stearate (AR) is used. The lubricant is used to improve processing fluidity and mold release properties.
[0102] S2, melt blending granulation:
[0103] Weigh each raw material according to the mass percentage. Add polylactic acid, polybutylene succinate, and the modified polyhydroxy fatty acid ester prepared in Example 1 to a high-speed mixer and mix at low speed for 3 minutes. Then add antioxidants and lubricants and continue mixing at high speed for 5 minutes to ensure that the additives are evenly dispersed and adsorbed on the surface of the resin particles, thus obtaining a premix. Then feed the premix into the hopper of a twin-screw extruder for melt extrusion. At the same time, accurately measure the rare earth strontium aluminate-coated cerium oxide core-shell powder prepared in Example 4 according to the mass percentage through a side feeder and add it to the melt in the third zone of the extruder. The specific process parameters of the twin-screw extruder are as follows:
[0104] Screw diameter: 40mm;
[0105] Length-to-diameter ratio (L / D): 40:1; Temperature setting (zone control):
[0106] Zone 1 (Feeding Zone): 150℃;
[0107] Second zone (melting zone): 165℃;
[0108] Third zone (side feeding zone): 170℃;
[0109] Zone 4 (Mixed Zone): 175℃;
[0110] Zone 5 (Mixed Zone): 175℃;
[0111] Zone 6 (Homogenization Zone): 170℃;
[0112] Zone 7 (Head): 165℃;
[0113] Screw speed: 200 rpm;
[0114] Vacuum exhaust: A vacuum vent is set between the fourth and fifth zones, with a vacuum level of -0.08 MPa, to remove moisture and small volatile molecules.
[0115] The resulting melt is extruded into strips through a die and cooled in a cooling water tank (water temperature 25℃). The cooled strips are then cut into uniform granules (average particle size 3mm) by a pelletizer and packaged for later use. The resulting granules are the biodegradable polyester plastics used in the production of landscape flower pots.
[0116] Example 8
[0117] A method for preparing biodegradable polyester plastic for landscape flowerpot production includes the following steps:
[0118] S1. Raw material preparation (by weight):
[0119] Polylactic acid (PLA): 60 parts. Injection molding grade PLA resin with a melt index (MFI, 190℃ / 2.16kg) of 5–15 g / 10 min was selected; in this example, NatureWorksInge™ 4032D was used. PLA resin provides basic rigidity and biodegradability.
[0120] Polybutylene succinate (PBS): 30 parts. A PBS resin with an intrinsic viscosity [η] of 1.2–1.8 dL / g was selected; in this example, Showa Denko Bionolle™ 1001MD was used. PBS resin primarily provides flexibility, impact toughness, and low-temperature performance.
[0121] Modified polyhydroxy fatty acid ester: 14 parts. In this example, the modified polyhydroxy fatty acid ester prepared in Example 2 was used.
[0122] Strontium aluminate-coated cerium oxide core-shell powder (SrAl2O4@CeO2): 1 part. In this example, the strontium aluminate-coated cerium oxide core-shell powder prepared in Example 5 was used.
[0123] Antioxidant: 0.5 parts. It is a compound of primary antioxidant 1010 (BASF) and secondary antioxidant 168 (BASF) at a mass ratio of 1:1.5. Antioxidants are used to delay the thermo-oxidative aging of materials during processing and use.
[0124] Lubricant: 1.0 part. Pentaerythritol tetrastearate is selected; in this example, Sinopharm Group pentaerythritol tetrastearate (95% purity) is used. The lubricant is used to improve processing fluidity and mold release properties.
[0125] S2, melt blending granulation:
[0126] Weigh each raw material according to the mass percentage. Add polylactic acid, polybutylene succinate, and the modified polyhydroxy fatty acid ester prepared in Example 2 to a high-speed mixer and mix at low speed for 5 minutes. Then add antioxidants and lubricants and continue mixing at high speed for 8 minutes to ensure that the additives are evenly dispersed and adsorbed on the surface of the resin particles, thus obtaining a premix. Then feed the premix into the hopper of a twin-screw extruder for melt extrusion. At the same time, accurately measure the rare earth strontium aluminate-coated cerium oxide core-shell powder prepared in Example 5 according to the mass percentage through a side feeder and add it to the melt in the third zone of the extruder. The specific process parameters of the twin-screw extruder are as follows:
[0127] Screw diameter: 40mm;
[0128] Length-to-diameter ratio (L / D): 40:1; Temperature setting (zone control):
[0129] Zone 1 (Feeding Zone): 155℃;
[0130] Second zone (melting zone): 170℃;
[0131] Third zone (side feeding zone): 175℃;
[0132] Zone 4 (Mixed Zone): 180℃;
[0133] Zone 5 (Mixed Zone): 180℃;
[0134] Zone 6 (Homogenization Zone): 175℃;
[0135] Zone 7 (Head): 170℃;
[0136] Screw speed: 300 rpm;
[0137] Vacuum exhaust: A vacuum vent is set between the fourth and fifth zones, with a vacuum level of -0.08 MPa, to remove moisture and small volatile molecules.
[0138] The resulting melt is extruded into strips through a die and cooled in a cooling water tank (water temperature 25℃). The cooled strips are then cut into uniform granules (average particle size 3mm) by a pelletizer and packaged for later use. The resulting granules are the biodegradable polyester plastics used in the production of landscape flower pots.
[0139] Example 9
[0140] A method for preparing biodegradable polyester plastic for landscape flowerpot production includes the following steps:
[0141] S1. Raw material preparation (by weight):
[0142] Polylactic acid (PLA): 70 parts. Injection molding grade PLA resin with a melt index (MFI, 190℃ / 2.16kg) of 5–15 g / 10 min was selected; in this example, NatureWorksInge™ 4032D was used. PLA resin provides basic rigidity and biodegradability.
[0143] Polybutylene succinate (PBS): 35 parts. A PBS resin with an intrinsic viscosity [η] of 1.2–1.8 dL / g was selected; in this example, Showa Denko Bionolle™ 1001MD was used. PBS resin primarily provides flexibility, impact toughness, and low-temperature performance.
[0144] Modified polyhydroxy fatty acid ester: 15 parts. In this example, the modified polyhydroxy fatty acid ester prepared in Example 3 was used.
[0145] Strontium aluminate-coated cerium oxide core-shell powder (SrAl2O4@CeO2): 1.2 parts. In this example, the strontium aluminate-coated cerium oxide core-shell powder prepared in Example 6 was used.
[0146] Antioxidant: 0.8 parts. It is a compound of primary antioxidant 1010 (BASF) and secondary antioxidant 168 (BASF) in a mass ratio of 1:2. Antioxidants are used to delay the thermo-oxidative aging of materials during processing and use.
[0147] Lubricant: 1.0 part. Pentaerythritol tetrastearate is selected; in this example, Sinopharm Group pentaerythritol tetrastearate (95% purity) is used. The lubricant is used to improve processing fluidity and mold release properties.
[0148] S2, melt blending granulation:
[0149] Weigh each raw material according to the mass percentage. Add polylactic acid, polybutylene succinate, and the modified polyhydroxy fatty acid ester prepared in Example 3 to a high-speed mixer and mix at low speed for 5 minutes. Then add antioxidants and lubricants and continue mixing at high speed for 8 minutes to ensure that the additives are evenly dispersed and adsorbed on the surface of the resin particles, thus obtaining a premix. Then feed the premix into the hopper of a twin-screw extruder for melt extrusion. At the same time, accurately measure the rare earth strontium aluminate-coated cerium oxide core-shell powder prepared in Example 6 according to the mass percentage through a side feeder and add it to the melt in the third zone of the extruder. The specific process parameters of the twin-screw extruder are as follows:
[0150] Screw diameter: 40mm;
[0151] Length-to-diameter ratio (L / D): 40:1; Temperature setting (zone control):
[0152] Zone 1 (Feeding Zone): 160℃;
[0153] Second zone (melting zone): 175℃;
[0154] Third zone (side feeding zone): 180℃;
[0155] Zone 4 (Mixed Zone): 185℃;
[0156] Zone 5 (Mixed Zone): 185℃;
[0157] Zone 6 (Homogenization Zone): 180℃;
[0158] Zone 7 (Head): 175℃;
[0159] Screw speed: 350 rpm;
[0160] Vacuum exhaust: A vacuum vent is set between the fourth and fifth zones, with a vacuum level of -0.08 MPa, to remove moisture and small volatile molecules.
[0161] The resulting melt is extruded into strips through a die and cooled in a cooling water tank (water temperature 35℃). The cooled strips are then cut into uniform granules (average particle size 4mm) by a pelletizer and packaged for later use. The resulting granules are the biodegradable polyester plastics used in the production of landscape flower pots.
[0162] Comparative Example 1
[0163] Comparative Example 1 served as the control group for Example 8. The modified polyhydroxy fatty acid ester prepared in Example 2 of Example 8 was replaced with the raw material polyhydroxy fatty acid ester (PHA, Ningbo Tianan Bio ENMAT Y1000P, melt index 3g / 10min (160℃)). The remaining raw materials, raw material amounts, and preparation steps remained consistent with those in Example 8, and finally, a polyester biodegradable plastic for the production of landscape flower pots was obtained.
[0164] Comparative Example 2
[0165] Comparative Example 2 served as the control group for Example 8. The modified polyhydroxy fatty acid ester prepared from the raw material in Example 8 in Example 2 was removed, while the remaining raw materials, raw material amounts, and preparation steps remained consistent with those in Example 8, ultimately yielding a biodegradable polyester plastic for the production of landscape flower pots.
[0166] Comparative Example 3
[0167] Comparative Example 3 served as the control group for Example 8. The rare earth strontium aluminate-coated cerium oxide core-shell powder prepared in Example 5 of Example 8 was replaced with raw material nano-cerium oxide (CeO2, particle size 50nm, purity 99.5%). The remaining raw materials, raw material amounts, and preparation steps remained consistent with those in Example 8, and finally, polyester biodegradable plastic for the production of landscape flower pots was obtained.
[0168] Comparative Example 4
[0169] Comparative Example 4 served as the control group for Example 8. The rare earth strontium aluminate-coated cerium oxide core-shell powder prepared in Example 5 was removed from the raw materials in Example 8. The remaining raw materials, raw material amounts, and preparation steps remained consistent with those in Example 8, and finally, polyester biodegradable plastic for the production of landscape flower pots was obtained.
[0170] Test Example 1
[0171] The performance of the biodegradable polyester plastics for producing landscape flower pots prepared in Examples 7 to 9 and Comparative Examples 1 to 4 was tested. The performance testing process is as follows, and the test results are shown in Table 1:
[0172] (1) Low temperature notched impact strength: Refer to GB / T 1843-2008 "Determination of impact strength of plastic cantilever beams" for specific test conditions and parameters as follows: -20℃, sample size 80×10×4mm, V notch.
[0173] (2) Yellowing test: Refer to GB / T 16422.2-1999 "Laboratory Light Source Exposure Test Methods for Plastics - Part 2: Xenon Arc Lamp" and the specific test conditions and parameters are as follows: Xenon lamp exposure yellowing test chamber for 1000 hours, and color difference (∆E) is measured by spectrophotometer.
[0174] (3) Flexural modulus: Refer to GB / T 9341-2008 "Determination of Flexural Properties of Plastics" for specific test conditions and parameters as follows: span 64mm, speed 2mm / min.
[0175] (4) Soil degradation rate: In accordance with the provisions of ISO 17556-2019 "Plastics - Determination of final aerobic biodegradability of plastic materials in soil", the specific test conditions and parameters are as follows: 25℃±1℃, humidity 60%RH, weight loss rate after 90 days of burial.
[0176] Table 1 Test Results
[0177] project Example 7 Example 8 Example 9 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Low temperature Charpy impact strength (-20 °C, kJ / m 2 )]]> 9.8 11.2 8.5 5.1 4.3 10.5 10.8 Color difference (∆E) 1.5 1.6 1.7 1.8 2.0 6.2 7.5 Flexural modulus (MPa) 2350 2200 2450 2100 2050 2180 2150 Soil 90-day weight loss rate (%) 15.2 16.8 14.5 16.5 17.0 25.3 28.5
[0178] Based on the data in Table 1, it can be seen that:
[0179] (1) Low temperature toughness:
[0180] Examples 7-9: Low-temperature notched impact strength ≥ 8.5 kJ / m 2 (Meets the impact resistance requirements of flower pots).
[0181] Comparative Example 1 (Unmodified PHA): Low-temperature notched impact strength decreased sharply by 53% (5.1 kJ / m). 2 vs 11.2kJ / m 2 This demonstrates that MAH modification is crucial for interface compatibility enhancement.
[0182] Comparative Example 2 (without PHA): Lowest low-temperature notched impact strength (4.3 kJ / m) 2 This demonstrates that the toughening effect of PHA is irreplaceable.
[0183] (2) Weather resistance:
[0184] Examples 7-9: ∆E≤1.7 (almost no yellowing), proving that rare earth strontium aluminate-coated cerium oxide core-shell powder has high UV resistance.
[0185] Comparative Example 3 (bare CeO2): ∆E=6.2 (severe yellowing), because CeO2 directly contacts the resin for catalytic photo-oxidation.
[0186] Comparative Example 4 (Strontium aluminate-coated cerium oxide core-shell powder without rare earth elements): ∆E=7.5 (worst), highlighting the decisive role of the core-shell structure in weather resistance.
[0187] (3) Rigid retention:
[0188] All groups had a flexural modulus >2000MPa (meeting the rigidity requirements of the flowerpot), proving that the PLA+PBS basic frame is effective.
[0189] The addition of modified polyhydroxy fatty acid ester / strontium aluminate-coated cerium oxide core-shell powder did not significantly reduce rigidity (Example 8: 2200 MPa vs Comparative Example 1: 2100 MPa).
[0190] (4) Degradation controllability:
[0191] Examples 7-9: 90-day weight loss rate ≤16.8% (stable during use).
[0192] Comparative Examples 3-4: Weight loss rate >25% (premature degradation), due to naked CeO2 catalytic hydrolysis / accelerated degradation without core-shell protection.
[0193] It should be noted that, in this document, terms such as “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0194] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A biodegradable polyester plastic for the production of landscape flower pots, characterized in that, Includes the following quantities of raw materials: 50-70 parts of polylactic acid; 20-35 parts of polybutylene succinate; 10-15 parts of modified polyhydroxy fatty acid ester; 0.8–1.2 parts of rare earth strontium aluminate-coated cerium oxide core-shell powder; Antioxidant 0.3–0.8 parts; Lubricant 0.5-1.0 parts; The modified polyhydroxy fatty acid ester is prepared by the following steps: Polyhydroxyalkanoate was pulverized to a particle size ≤1mm and vacuum dried at 50-80℃ for 5-6h to obtain dried polyhydroxyalkanoate. Then, maleic anhydride and dicumyl peroxide were mixed and dissolved in acetone to prepare a 10wt% modification solution. The dried polyhydroxyalkanoate was added to a co-rotating twin-screw extruder, and the modification solution was injected into it for extrusion. The resulting extruded strips were then water-cooled, pelletized, extracted with acetone, and vacuum dried to obtain modified polyhydroxyalkanoate. The polyhydroxy fatty acid ester is model number Ningbo Tianan Bio ENMAT Y1000P; The rare earth strontium aluminate-coated cerium oxide core-shell powder is prepared by the following steps: B1. Dissolve strontium nitrate and aluminum nitrate in deionized water, then add citric acid and sonicate for 20-30 minutes to obtain a strontium aluminum solution; in another container, disperse nano-cerium oxide in deionized water and sonicate for 20-30 minutes to obtain a cerium oxide suspension. B2. Slowly add the strontium aluminum solution dropwise into the cerium oxide suspension. After the addition is complete, stir at a constant temperature of 55-60℃ for 20-30 minutes. After that, add ammonia water to adjust the pH to 9.0 and let it stand to form a gel. B3. The gel was aged at room temperature for 24 hours, then dried at 100°C for 12 hours. After drying, it was ground through a 100-mesh sieve and then calcined in a muffle furnace at 580-600°C for 2 hours. It was then naturally cooled to room temperature to obtain rare earth strontium aluminate-coated cerium oxide core-shell powder.
2. The biodegradable polyester plastic for producing landscape flower pots according to claim 1, characterized in that, The maleic anhydride and dicumyl peroxide are mixed at a mass ratio of 6 to 12:
1.
3. The biodegradable polyester plastic for producing landscape flower pots according to claim 1, characterized in that, The temperature gradient of the co-rotating twin-screw extruder is as follows: feeding zone 125-130℃, melting zone 140-145℃, reaction zone 150-155℃, and homogenization zone 140-150℃.
4. The biodegradable polyester plastic for producing landscape flower pots according to claim 1, characterized in that, The ratio of strontium nitrate, aluminum nitrate, deionized water, and citric acid in B1 is 0.2 mol: 0.8 mol: 500 mL: 1.0–1.2 mol; the ratio of nano-cerium oxide and deionized water in B1 is 100 g: 500 mL.
5. The biodegradable polyester plastic for producing landscape flower pots according to claim 1, characterized in that, The antioxidant is a compound of primary antioxidant 1010 and secondary antioxidant 168 in a mass ratio of 1:1 to 2.
6. The biodegradable polyester plastic for producing landscape flower pots according to claim 1, characterized in that, The lubricant is calcium stearate or pentaerythritol tetrastearate.
7. A method for preparing a biodegradable polyester plastic for producing landscape flower pots according to any one of claims 1 to 6, characterized in that, The process includes the following steps: Weigh each raw material according to the mass percentage, mix polylactic acid, polybutylene succinate and modified polyhydroxy fatty acid ester for 3-5 minutes, then add antioxidants and lubricants, and continue mixing for 5-8 minutes to obtain a premix. Then, put the premix into a twin-screw extruder for melt extrusion, and at the same time add rare earth strontium aluminate coated cerium oxide core-shell powder. After extrusion, cooling and pelletizing, the resulting melt is used to obtain a biodegradable polyester plastic for the production of landscape flower pots.
8. The method for preparing a biodegradable polyester plastic for landscape flowerpot production according to claim 7, characterized in that, The process parameters of the twin-screw extruder are as follows: The twin-screw extruder has a screw diameter of 40 mm; a length-to-diameter ratio of 40:1; a screw speed of 200–350 rpm; and zone temperatures of the twin-screw extruder as follows: Zone 1 150–160℃, Zone 2 165–175℃, Zone 3 170–180℃, Zone 4 175–185℃, Zone 5 175–185℃, Zone 6 170–180℃, and Zone 7 165–175℃.
Citation Information
Patent Citations
Biodegradable polycarbonate butylene terephthalate composite material and preparation method of biodegradable polycarbonate butylene terephthalate composite material
CN102153838A
Modified PLA full-degradable plastic and preparation method thereof
CN112920566A